Electrical Properties and Impedance Spectroscopy of Pure and Copper-Oxide-Added Potassium Sodium Niobate Ceramics - Alkoy, Ebru Mensur; Berksoy-Yavuz, Ayse (IEEE-Inst Electrical Electronics Engineers Inc, 2012)
Pure and 1 mol% CuO-added lead-free potassium sodium niobate K0.5Na0.5NbO3 (KNN) ceramics were prepared by the conventional solid-state calcination method. Copper oxide was mainly used as a sintering aid in the KNN structure. Microstructural analyses clearly showed that the CuO formed a secondary phase at the grain boundaries. Impedance spectroscopy was used as a tool to analyze the electrical behavior of KNN ceramics as a function of frequency from 100 Hz to 10 MHz at various temperatures. The impedance studies proved that CuO led to the formation of a secondary grain boundary phase, as well as creation of highly mobile point defects. The relaxation time of copper-added samples was less than that of pure KNN. This shorter time indicated a higher space charge mobility for CuO-added samples. The thermal activation energy for relaxation of charge carriers (E-g) was calculated as 0.73 eV for CuO-added samples.
Keywords: Piezoelectric Properties